ENGLISH LANGUAGE URGENCY FOR TOURISM AND HOSPITALITY EMPLOYEES TO BOOST GLOBAL ECONOMY - Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti; Nengah Dwi Handayani; Anak Agung Istri Yudhi Pramawati (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Having good communication skills is important for all tourism and hotel employees to have. All tourism and hospitality employees are expected to be effective and efficient English speakers to provide quality services. The present study was conducted to explore the needs of English among hospitality employees to improve the global economy. The results showed that high language competence is needed by hospitality employees to be able to work professionally. It is, however, most hospitality employees still have problems in English. Consequently, they are unable to communicate effectively to satisfy tourists’ expectations. The study implies that the increase of English language training needs to be carefully considered and the English learning syllabus offered by hospitality training institutions needs to restructured to improve career choices in the tourism industry.